1969
DOI: 10.2134/agronj1969.00021962006100040026x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Irrigation Interval and Plant Density on Alfalfa Seed Production1

Abstract: Irrigation applied once every 2 weeks, providing a seasonal total of 25.7 cm of water, produced the greatest seed yield, as well as an increase in the number of pods per raceme, number of seeds per pod, and 1,000‐seed weight. Plants irrigated at 3 or 4‐week intervals produced the highest number of hard seeds. The 50 ✕ 50 cm plant spacing produced well developed alfalfa plants which gave relatively high seed yields of 80 kg/dunum (1,000 m2) in 1966 and 65 kg/dunum in 1967. The variety ‘Hairy Peruvian’ produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
2

Year Published

1972
1972
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 2 publications
1
19
1
2
Order By: Relevance
“…Abu-Shakra et al (1977) showed that seed yield was significantly affected by the number of forage harvests prior to seed production, and this effect was mainly associated with variation in the number of fertile stems per plant and pods per raceme. Abu-Shakra et al ( 1969) and Askarian et al (1995) reported similar effects as a consequence of different row spacing. According to Fougereux et al (1997) little is known about the factors that are responsible for differences in physiological quality between seed lots at harvest.…”
Section: Introductionmentioning
confidence: 73%
“…Abu-Shakra et al (1977) showed that seed yield was significantly affected by the number of forage harvests prior to seed production, and this effect was mainly associated with variation in the number of fertile stems per plant and pods per raceme. Abu-Shakra et al ( 1969) and Askarian et al (1995) reported similar effects as a consequence of different row spacing. According to Fougereux et al (1997) little is known about the factors that are responsible for differences in physiological quality between seed lots at harvest.…”
Section: Introductionmentioning
confidence: 73%
“…Abu-Shakra, S., Akhatar, M., & Bray, D. W. (1968 Sažetak: U radu se analiziraju najvažniji proizvodni i ekonomski rezultati koji se ostvaruju u prozvodnji semena lucerke na porodičnim poljoprivrednim gazdinstvima u R. Srbiji. Proizvodnju semena lucerke karakterišu relativno niska ulaganja po jedinici površine (499,83 € ha -1 ), ali uprkos tome, u ovoj proizvodnji ostvaruju se vrlo dobri ekonomski pokazatelji (marža pokrića 807,00 € ha -1 ; koeficijent ekonomičnosti 2,47; stopa dobiti 59,56%).…”
Section: Farmunclassified
“…Still, domestic producers' lack of knowledge on production technology of this useful and cost-effective perennial crop is concerning. It is necessary to educate producers through advisory service, producers' union, media, etc., so as to enable farmers to realize the full economic potential of alfalfa production.Abu-Shakra, S., Akhatar, M., & Bray, D. W. (1968 Sažetak: U radu se analiziraju najvažniji proizvodni i ekonomski rezultati koji se ostvaruju u prozvodnji semena lucerke na porodičnim poljoprivrednim gazdinstvima u R. Srbiji. Proizvodnju semena lucerke karakterišu relativno niska ulaganja po jedinici površine (499,83 € ha -1 ), ali uprkos tome, u ovoj proizvodnji ostvaruju se vrlo dobri ekonomski pokazatelji (marža pokrića 807,00 € ha -1 ; koeficijent ekonomičnosti 2,47; stopa dobiti 59,56%).…”
unclassified
“…However, Dunbier et al (1983) recommended a sowing rate of 1 kg/ha and row spacing of 75 cm, although they produced no evidence to support these recommendations. Experiments conducted overseas, especially in the United States, have shown that high seed yields were obtained from lucerne sown at rates ranging from 0.5 to 2 kg/ha and in rows from 60 to 150 cm apart (Abu-Shakra et al 1969;Goplen 1972).…”
Section: Introductionmentioning
confidence: 99%